The Role Of Milk Peptide As Antimicrobial Agent In Supporting Health Status - Eni Kusumaningtyas (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Antimicrobial peptide is commonly present in all species as a component of their innate immune defense against infection. Antimicrobial peptides derived from milk such as isracidin, casocidin, casecidin and other fragments with variety of amino acid sequence are released upon enzymatic hydrolysis from milk protein К-casein, α-casein, β-casein, α-lactalbumin and β- lactoglobulin. These peptides were produced by the activity of digestive or microbial protease such as trypsin, pepsin, chymosin or alcalase. The mode of action of these peptides is by interaction of their positive with negative charge of target cell membrane leading to disruption of membrane associated with physiological event such as cell division or translocation of peptide across the membrane to interact with cytoplasmic target. Modification of charged or nonpolar aliphatic residues within peptides can enhance or reduce the activities of the peptides against a number of microbial strains and it seems to be strain dependent. Several peptides act not only as an antimicrobial but also as an angiotensin-converting enzyme inhibitor, antioxidant, immunomodulator, antiinflamation, food and feed preservative. Although the commercial production of these peptides is still limited due to lack of suitable large-scale technologies, fast development of some methods for peptide production will hopefully increase the possibility for mass production.   Key words: Peptide, antimicrobial, milk